A Study on the Impact of Shorting Mechanism on the Degree of Divergence of Investors' Opinions - Based on the Perspective of Listed Companies - Liu, Zhaoyang (International Journal of Global Economics and Management, 2024)
This paper thoroughly investigates the impact of shorting mechanism on the degree of divergence of opinions among investors, and takes listed companies as the subject of the study. Through the method of empirical analysis, this paper reveals the intensifying effect of shorting mechanism on the disagreement among investors, especially in the complex and changing market environment, this effect is more significant. This finding not only provides a decision-making reference for investors, but also provides a theoretical basis for market regulators to formulate policies, which is of great significance for promoting the stability and healthy development of the market.